Demand and Requirements for a Digital Healthcare System to Manage Gestational Diabetes in Patients and Healthcare Professionals: A Cross-sectional Survey - Jin Yu MD; Oyoung Kim MD; Byung Soo Kang MD, PhD; Seon Ui Lee MD; Youn Ju Lee MS; Han Sung Hwang MD, PhD; Seung Mi Lee MD, PhD; Seung Chul Kim MD, PhD; Yoon-Hee Choi MD, PhD; Hyun Sun Ko MD, PhD (SAGE Publishing, 2024)
This study aimed to assess the current status of gestational diabetes mellitus (GDM) diagnosis and management, and the demand for a digital healthcare system, in order to develop an optimal digital-based management model for GDM. An anonymous online survey was conducted targeting pregnant/postpartum women (Group W), internal medicine physicians (Group P), and obstetricians (group O) from September 6, 2022 to December 31, 2022. The survey assessed the women's knowledge of GDM and gathered information about healthcare professionals' (HCPs) current GDM management practices. All groups were asked about their acceptance of and demands for a digital healthcare system for GDM. Statistical comparisons between groups were conducted using the chi-square test or Fisher's exact test where appropriate. A total of 168 participants were in Group W, 185 in Group P, and 256 in Group O. Participants from all groups recognized the need for a digital healthcare system for GDM (Group W: 95.8%, Group P: 85.9%, Group O: 60%). However, HCPs showed less willingness to integrate these systems into their clinics than pregnant/postpartum women. Essential features identified were recording blood glucose levels and insulin, along with automatic data linkage from self-monitoring devices. Group W showed a higher preference for lab test access, search functionality, and fetal weight assessment than groups P and O (all P  < .0001), while Groups P and O had a greater preference for recording insulin and maternal body weight compared to Group W ( P  = .0141 and .0023, respectively). Both pregnant/postpartum women and HCPs acknowledged the benefits of utilizing a digital healthcare system for managing GDM. However, there were differences in perspectives among these groups.